Design of Male Student Dormitory Medan State University with Appropriate Site Development Concept (Green Architecture) - Dwira Nirfalini Aulia; Annisa Anindita Nasution (International Journal of Architecture and Urbanism, 2021)
Student dormitories are the residential neighborhood as student residences during their lectures. The dorms are increasing as students access different regions to study at a university. Medan city has several dorms which one is of Medan State University. This student dormitory is a special dormitory for male students of Medan State University who come from areas in North Sumatra. The condition of the dormitories is considered inadequate as a Student dormitories capacity is less than required. The existing student dormitory facilities are not complete for student dormitory facilities. It is necessary to design the male student dormitory of Medan State University. In this design, the Medan State University male student dormitory requires additional supporting facilities around the student dormitory and good building conditions. The location of the building is in the educational Area on Jalan William Iskandar Pasar V, New Memories, Percut Sei Tuan. The Male Student Dormitories applies green architecture with a basic concept approach to land use which is considered to respect every criterion contained in the land, made as comfortable as possible, responsive to the factors evaluated at the construction site.